KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK COOKIES DENGAN PENAMBAHAN PUREE LABU KUNING DAN TEPUNG CANGKANG TELUR AYAM - Suryati Suryati; Maherawati Maherawati; Lucky Hartanti (Universitas Tanjungpura, 2019)
Cookies are a popular snack for people. Additional of plk (pumkin puree) and tct (eggshell flour) will increase the nutritional value of cookies. The aims of this study is to determine the chemical and organoleptic characteristics of cookies made from pumpkin puree and chicken eggshell flour. The research using a Complete Randomized Block Design (CRBD) with singel factor that was the addition of eggshell flour and pumpkin puree (5:55, 7:53, 9:51, 11:49, 13:47, 15:45) and each treatment repeated 4 times so that 24 treatment combinations obtained. Data was analyzed statistically by using the ANOVA test, continued by HSD test. Organoleptic data was analyzed by Kruskall Walis test. The addition of pumpkin puree and chicken eggshell flour did not affect the water content, color, taste and overall preference level of the cookies produced, but did affect ash content, calcium levels and texture of cookies. Based on the effectiveness test (De Garmo), the best cookies are produced from a ratio of 7% chicken eggshell flour and 53% pumpkin puree with chemical characteristics : water content 4.206%, ash content 0.865%, calcium content 3.767%, texture 0.607 Kg Force, color 3.433 (likes), taste 3,533 (likes) and an overall average value of 3,600 (likes).